Development of fish bars as a high zinc and calcium snack made from bilih fish (Mystacoleuseus padangensis Blkr) flour - Elnovriza, Deni; Riyadi, Hadi; Rimbawan, Rimbawan; Damayanthi, Evy; Winarto, Adi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The study analysed differences in nutrition content of various bilih fish flour proportions in bilih fish bar with zinc and calcium as minerals of interest. The study used a Completely Randomized Design (CRD). The proportion of bilih fish flour in the fish bars dough were of three levels, i.e. 30%, 40% and 50% of the total weight of flour. The data obtained were analyzed with one-way ANOVA, followed by Duncan's New Multiple Range test. The level of statistical significance was set at p<0.05. The best proportion based on its nutritional content was the 50% with the energy content of 327 kcal, protein content 22.75%, lipid content 11.99%, carbohydrate content 32.06%, moisture content 28.28%, ash content 4.44%, zinc content 4.58 mg, and calcium content 922.23 mg per 100 g. A serving size (±30 g) of treatment is able to suffice for 5.06-7.05% zinc and 0.87-16.77% calcium adequacy as well as the daily requirement of 2,150 kcal. Sensory evaluation showed that the treatments had no significant effects on the organoleptic attributes of the fish bars, except for taste (0.033). This bilih fish bar can be utilized as a source of zinc and calcium for high-risk groups such as children, adolescents, pregnant women, and people with diabetes.